Moisture loss rate drives the species‐specific sensitivity of shoot flammability to water status - Mahmud, Azaj; Aktepe, Nursema; Schwilk, Dylan W. (Wiley, 2025)
Abstract Premise The importance of live fuel moisture content (LFMC), a critical determinant of plant flammability, to crown‐fire behavior is subject to debate; physiological mechanisms underlying LFMC dynamics need to be incorporated into fire behavior models to better understand wildfire and vegetation–fire feedback. Here we aimed to determine the relationships among water potential, LFMC, and flammability, and how ecophysiological traits related to LFMC dynamics influence the relationship between plant water status (measured as water potential and LFMC) and flammability across nine native shrubs in Texas. Methods We assessed ignitability and heat release on excised shoots across a wide range of water potential and measured leaf and shoot ecophysiological traits to answer two questions: (1) What are the relationships between water potential, LFMC, and flammability, and do they vary across species? (2) If the relationship between water status and flammability varies across species, which plant traits predict the strength of this relationship? Results LFMC covaried with water potential, but the shape of this relationship varied across species. The effect of water status on ignitability and heat release varied significantly across species, and the shoot moisture loss rate was lower in species in which ignitability and heat release was sensitive to water status. Conclusions This study suggests that the LFMC–flammability relationship across species depends on plant traits that influence water loss during fire weather conditions, and incorporating plant traits shaping LFMC dynamics into fire behavior models will improve our understanding of drought–vegetation–fire feedback.